2002
DOI: 10.1152/ajplung.00012.2002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation contribute to lung toxicity after a common breast cancer chemotherapy regimen

Abstract: . Oxidative stress and inflammation contribute to lung toxicity after a common breast cancer chemotherapy regimen. Am J Physiol Lung Cell Mol Physiol 283: L336-L345, 2002. First published March 29, 2002 10.1152/ ajplung.00012.2002-Delayed pulmonary toxicity syndrome after high-dose chemotherapy (HDC) and autologous hematopoietic support occurs in up to 64% of women with advanced-stage breast cancer. Using a similar, but nonmyeloablative, HDC treatment regimen in mice, we found both immediate and persistent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…14 Some of the toxic effects of chemotherapy drugs are caused by the increased production of infl ammatory mediators. 15,16 Consistent with previous studies, we demonstrated that AraC caused infl ammatory cell Fig. 1A-D. The effect of sodium zinc dihydrolipoylhistidinate against cytosine arabinoside-induced alopecia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…14 Some of the toxic effects of chemotherapy drugs are caused by the increased production of infl ammatory mediators. 15,16 Consistent with previous studies, we demonstrated that AraC caused infl ammatory cell Fig. 1A-D. The effect of sodium zinc dihydrolipoylhistidinate against cytosine arabinoside-induced alopecia.…”
Section: Discussionsupporting
confidence: 89%
“…Chemotherapy also increases oxidative stress, 16 which is associated with infl ammation. 20 High levels of ROS activate the oxidant-sensitive nuclear transcription factor NF-κB, thereby upregulating infl ammatory cytokine expression.…”
Section: Discussionmentioning
confidence: 99%
“…Glutathione peroxidase activity in BAL fluid was determined by using the Bioxytech GPx-340 kit (Oxis International) according to the manufacturer's instructions with minor modifications. Plasma glutathione peroxidase activity was measured as described previously (26). GST activity in BAL fluid and plasma was measured using a Bioxytech GST-340 kit (Oxis International) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Carmustine can cause pulmonary toxicity, usually in the form of interstitial pneumonitis, possibly due to the inhibition of glutathione reductase in alveolar macrophages; melphalan can have pulmonary toxicity as well. [15][16][17] The dose-escalation schema and trial design were linked with serial assessments of pulmonary function. 18,19 We report minimal pulmonary toxicity at the highest planned dose level (melphalan 200 mg/m 2 ) with a 49% rate of complete and near complete responses (CR).…”
Section: Introductionmentioning
confidence: 99%